Language Under the Veil: An Intertextual Reading of Lament for Ugljesha the Youth (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Paper is dealing with the first work by medieval Serbian poetess, princess Jelena Serska (often called “Jefimija the Nun”), concentrating on one aspect of its intertextual liaisons – the classical and Byzantine threnody tradition, leaving aside other intertextual possibilities, the iconophilic and stoic traditions included. This poem is deeply integrated in the classical-Byzantine heritage. However, the poem significantly varies from the topos mater dolorosa as it is expressed in various genres, especially in threnody epigrams of the Greek Anthology. This disharmony represents the key-opportunity for a deeper hermeneutical insight: it leads to the revealing of the authentic poetic Self, first by confronting the classical and Christian perception of being, then by confronting the Christian onto-anthropology with the idiosyncratic identity of the poetess.
Keywords: princess Jelena Serska (“Jefimija the Nun”); intertextuality; threnody; identity